Dairy farm households, processor linkages and household income: The case of dairy hub linkages in East Africa - Rao, E.J.O.; Omondi, Immaculate A.; Karimov, A.A.; Baltenweck, Isabelle (Brill, 2016)
In this study we have analysed the effects of household linkages to milk market via dairy hubs currently implemented under the East African Dairy Development project. Our analyses show that participation in dairy hubs increases dairy revenues by USD 1,022 on average. Impacts are higher for households participating in hubs supplying exclusively to processors (USD 1,673) relative to ones supplying hubs that pursue mixed-linkage approach. Moreover, participation in dairy hubs also yields significant effect on household income. Appropriate measures should be undertaken to widen the reach of such processor linkages while also safeguarding existing gains, more so as the processing sector becomes more concentrated.